Understanding psychological factors behind motorcyclists crossing behavior on undivided roads in mixed traffic conditions: A case study of Hau Giang, Vietnam - Hai Ngoc Duong; Minh Cong Chu; Nathan Huynh (IATSS Research, 2025)
Motorcycle crashes are a common occurrence in developing countries with mixed traffic. A contributing factor to these crashes is the crossing maneuvers of motorcyclists on undivided roadways. This study applies the Theory of Planned Behavior to understand the intentions and behaviors of these motorcyclists when making such maneuvers. It utilizes data from two surveys conducted in Hau Giang, Vietnam in 2022. The first investigation surveyed 351 participants to elicit the motorcyclists' behavioral beliefs and control beliefs when making crossing maneuvers that complied with traffic rules (complying maneuvers, CM), and the second investigation interviewed 260 respondents to elicit motorcyclists' beliefs when making crossing maneuvers that violated traffic rules (illegal maneuvers, IM). By applying the Structural Equation Modeling approach, the results reveal that the intention of motorcyclists to perform crossing maneuvers (CMs) is influenced by facilitating circumstances, subjective norms, and descriptive norms. In contrast, the intention to perform improper maneuvers (IMs) is driven by advantage beliefs, descriptive norms, facilitating circumstances, subjective norms, and driving situation awareness. Additionally, risk perception directly affects motorcyclists' performance of CMs, while near-miss incidents related to IMs are directly influenced by facilitating circumstances and perceived risk. These findings suggest that reducing improper maneuvers and promoting safer road-crossing performance can be achieved through targeted safety intervention strategies. Such strategies could include addressing the consequences of advantage beliefs regarding IMs and enhancing riders' situation awareness and risk perception through driver education and training programs.